2004
DOI: 10.1002/art.20433
|View full text |Cite
|
Sign up to set email alerts
|

Antiphospholipid syndrome nephropathy in patients with systemic lupus erythematosus and antiphospholipid antibodies: Prevalence, clinical associations, and long‐term outcome

Abstract: Objective. To evaluate the prevalence, clinical associations, and outcome of antiphospholipid syndrome (APS) nephropathy in patients with systemic lupus erythematosus (SLE) and antiphospholipid antibodies (aPL) and in SLE patients without aPL.Methods. Kidney biopsy specimens obtained from 81 patients with aPL (18 of whom had APS) and 70 patients without aPL were retrospectively examined for the presence of APS nephropathy. Clinical and serologic data obtained at the time of kidney biopsy and during a mean foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
163
2
7

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(186 citation statements)
references
References 31 publications
11
163
2
7
Order By: Relevance
“…The prevalence of "aPL-nephropathy" in SLE patients without aPL varies between 4%-16 %, whereas 25%-39% of the aPL-positive SLE patients have "aPL-nephropathy" (92,94 Catastrophic antiphospholipid syndrome Encountered in less than 1% of APS patients, catastrophic APS is characterized by accelerated widespread small/medium vessel thromboses with unusual organ involvement and has a mortality of 30%-50% despite aggressive multimodal intensive treatment (102)(103)(104).…”
Section: Renal Impairmentmentioning
confidence: 99%
“…The prevalence of "aPL-nephropathy" in SLE patients without aPL varies between 4%-16 %, whereas 25%-39% of the aPL-positive SLE patients have "aPL-nephropathy" (92,94 Catastrophic antiphospholipid syndrome Encountered in less than 1% of APS patients, catastrophic APS is characterized by accelerated widespread small/medium vessel thromboses with unusual organ involvement and has a mortality of 30%-50% despite aggressive multimodal intensive treatment (102)(103)(104).…”
Section: Renal Impairmentmentioning
confidence: 99%
“…The improved blood flow of the grafted kidney after 3 months with continuous anticoagulation therapy also suggested the APSN. APSN is usually associated with a catastrophic functional outcome in the first posttransplant year (5). However in our case, renal function was improved dramatically with the appropriate anticoagulation therapy after the early detection of allograft APSN.…”
Section: Discussionmentioning
confidence: 55%
“…Antibodies should be demonstrable on at least two occasions separated by 12 weeks(1). These antibodies may be associated with connective tissue diseases such as systemic lupus erythematosus (secondary APS) or be found in isolation (primary APS) (5). However, the most recent international consensus statement on classification criteria for APS advises against this terminology because the clin-ical consequences in both groups appear to be the same (5).…”
Section: Discussionmentioning
confidence: 99%
“…The association between aPL and membranous glomerulonephritis (class V) seems unclear, as it has been reported in some studies and anecdotal case reports,24-26 but not confirmed in others. 17,27 In 2002, Daugas et al14 performed a retrospective study of 114 patients with lupus who had undergone renal biopsy. APS nephropathy was observed in 32% of patients with SLE, irrespective of lupus nephritis.…”
Section: Aps Nephropathymentioning
confidence: 99%
“…Indeed, APS nephropathy was associated with positive tests for lupus anticoagulant and antibodies against cardiolipin. 17 The same study evaluated the progression of APS nephropathy through analysis of serial kidney biopsy findings. Evolution from acute thrombotic features to chronic thrombotic disease characterized by proliferative, obstructive and fibrotic lesions was found.…”
Section: Arterial Hypertensionmentioning
confidence: 99%